2012
DOI: 10.1063/1.3681920
|View full text |Cite
|
Sign up to set email alerts
|

Valence and inner-valence shell dissociative photoionization of CO in the 26–33 eV range. II. Molecular-frame and recoil-frame photoelectron angular distributions

Abstract: Experimental and theoretical results for molecular-frame photoemission are presented for inner-valence shell photoionization of the CO molecule induced by linearly and circularly polarized light. The experimental recoil frame photoelectron angular distributions (RFPADs) obtained from dissociative photoionization measurements where the velocities of the ionic fragment and photoelectron were detected in coincidence, are compared to RFPADs computed using the multichannel Schwinger configuration interaction method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 82 publications
1
12
0
Order By: Relevance
“…A notable difference with our results is the absence of Feshbach resonances in all previously reported calculations, except for a few resonances predicted by the MCSCI method. 47 At higher energies, the XCHEM results are compatible with those of other calculations. These results support the notion that our description of the nonresonant part of the electronic continuum is reliable also in the region where Feshbach resonances appear.…”
Section: Resultssupporting
confidence: 83%
“…A notable difference with our results is the absence of Feshbach resonances in all previously reported calculations, except for a few resonances predicted by the MCSCI method. 47 At higher energies, the XCHEM results are compatible with those of other calculations. These results support the notion that our description of the nonresonant part of the electronic continuum is reliable also in the region where Feshbach resonances appear.…”
Section: Resultssupporting
confidence: 83%
“…The main configurations of this satellite peak include 5σ −2 1π * (∼64%), 4σ −1 5σ −1 1π * (∼21%), and 5σ −2 2π * (∼6%), which are consistent with MCS-CI and SAC-CI results. [91,92] Compared to the early Green's function/CI studies of the inner-valence ionization of N 2 and CO molecules [91,92,96,100,101], the GFCC-i(2,3) calculation exhibits better agreement than the GFCCSD calculation in terms of overall spectral function profile (that is, the consistent prediction of the significant satellite peaks). Note that the previous Green's function study [96] is able to provide more detailed information of the inner valence ionization by providing the positions of weaker satellite peaks which might not be observable in our present GFCC calculations.…”
Section: Resultsmentioning
confidence: 92%
“…The most detailed information is ideally embodied in the molecular frame angular distributions (MFPADS) that probe in great detail the dynamic of the ionization. A comprehensive investigation has been conducted only in CO [11]. A recent study of the H 2 molecule has shown the potential to image correlation contributions to the ground state wavefunction [12].…”
Section: Introductionmentioning
confidence: 99%